THE MAIN FUNCTIONS OF WATER TREATMENT PLANTS AND WATER TREATMENT PROCESSES - Madiyarov Allayar Azatovich; Qurbaniyazov Alisher Jalgashovich; Joldasbayev Miyratdiyn Sultamurat-uli; Orazbaev Abbaz Rashitovich (Journals Park Publishing, 2023)
The article is devoted to the study of the operation and supervision of water treatment facilities and water treatment processes. Analysis of water in Central Asia, drinking water in Uzbekistan and scientific results in regulatory documents.
Keywords: process, hydroecology, standards, disinfection, water supply.